THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE ON ENVIRONMENTAL DISCLOSURE AND ECONOMIC PERFORMANCE (EMPIRICAL STUDY IN BURSA EFEK INDONESIA) - Susanto, Barkah (Universitas Muhammadiyah Magelang, 2008)
This research is carried out becaused there is some previous resuls of the research are contrastive. It concerns on the relationship between environmental performance, environmental disclosure and economicperformance. The objectives of this research are toprove empirically the influence of environmental performance on environmental diclosure and the influence of environmental performance on economic performance to he condition of Indoneisa. The samples of this research are 17 entriprises which are registered in Bursa Efek Indonesia that follow PROPER in the year 205 2007. The type of data analysis are collecting data and the technique of analyzing data used fixed and or common effect. The result of this research is showed that the environmental performance has positive significance influence on environmental disclosure, and the other hand, the environmenal performance has not positive significance influence on economic performance.